2021
DOI: 10.7150/thno.48152
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Sart1 to modulate macrophage polarization by siRNA-loaded liposomes: a promising therapeutic strategy for pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic and diffuse form of interstitial lung disease of unknown etiology with a fatal outcome. Although various strategies for IPF have been developed over the last few decades, no significant positive impact on the prognosis of IPF has been observed. According to the current paradigm, macrophages have been recognized to play a significant role in IPF pathogenesis. Here, we report a potential nanomedicine-based gene therapy for IPF based on regulate macrophage polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 52 publications
2
49
0
Order By: Relevance
“…DiI-loaded liposomes were prepared as previously described (28). The mice were intraperitoneally injected with liposomes and anesthetized at different time points.…”
Section: In Vivo Biodistribution Of the Liposomesmentioning
confidence: 99%
“…DiI-loaded liposomes were prepared as previously described (28). The mice were intraperitoneally injected with liposomes and anesthetized at different time points.…”
Section: In Vivo Biodistribution Of the Liposomesmentioning
confidence: 99%
“…Although numerous clinical trials have been carried out to characterize viable drugs for IPF, unfortunately, no effective therapeutic approach was currently available to cure or even halt the progression of IPF 31 . Previous studies 30 , 36 , including our 15 , have illustrated that liposomes loading with siRNA are established as drug carriers for airway injection owing to their safety and effectiveness to provide controlled drug release in the lung. Inspiringly, patisiran, the first siRNA drug based on liposomes, was approved by the FDA in 2018, moving the concept to clinical settings 37 .…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies 13 , 14 , including ours 15 , demonstrated that cationic liposomes are promising strategies for the siRNA-based therapy of various disease. Especially for pulmonary fibrosis, we have verified that liposomes administrated by intratracheal injection, equivalent to clinical atomization treatment, preferred to accumulate in the fibrotic lesion, in which consists of abundant fibroblasts and/or myofibroblasts.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The authors report a dose-dependent decrease of CD206, TGF-β and α-SMA expression in bleomycin-induced fibrosis. Another approach reported liposome-mediated delivery of siRNA against spliceosome associated factor 1 ( Sart1 ), which was shown to be involved in oxygen-independent HIF-1α degradation and macrophage M2 polarization, to attenuate M2 macrophage polarization in fibrotic lungs [ 85 ]. Additionally, a novel phosphodiesterase 4 (PDE4) inhibitor has been tested for antifibrotic effects in a bleomycin-induced mouse model [ 86 ].…”
Section: The Implication Of Ams In Lung Diseasesmentioning
confidence: 99%